Kelayakan Finansial Usaha Gula Aren Dikecamatan Culamega Kabupaten Tasikmalaya - Muhammad, Asy’ari; Jakiyah, Ulpah; Fitriadi, Budhi Wahyu (PT Maju Malaqbi Makkarana, 2024)
Palm sugar is a commodity produced from the sugar palm plant. Palm sugar has been known to the public since long ago. Palm sugar is produced from tapping palm sap which is then filtered and cooked and then thickened. Based on its purpose to determine the income and revenue and to determine how financially feasible the palm sugar business is. This research was conducted in Culamega District, Tasikmalaya Regency. Determination of the location using census sampling Census sampling which is drawn randomly at the research site, namely in Culamega District with a sample of 10 palm sugar craftsmen from each village in Culamega District, 2 samples of palm sugar craftsmen or entrepreneurs were taken each with the characteristics of more than 5 years as a palm sugar entrepreneur. The results of the study showed that the average income of the palm sugar business in Culamega District was IDR 4,579,056.36. with an R / C Ratio value of 5.28, meaning that the profit received by each palm sugar business manager will get a profit of 52.8% so that it can be said that the average palm sugar processing business in the research area is feasible to be pursued.